(3UdI GdCgd HJOhjf eG JaQb ef efGbH Hfi aVds - (3eMeO Hf YhV Hf eMeO Hf SGde HGaVd, HGaVd,J (B1340 (3g` s
(3ChdgG (B:s
(3hHYO , ajbhd GdabjQ Edi QHg GdMce GdYOd eMeO Hf YhV Hf eMeO HGaVd Ef PcQ efGbH GdUGdMjf s
(3BNQgG (B:s
(3QhM SQJ ef gjcd fhQGfi eMahaI HedGFc GdQMef s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3ai JQGLe hefGbH Bd HGaVd ai MVQehJs
(3HChdgG hBNQgG JbQjX hJbjjOGJ HYVgG dg ajeI s
(3hcJHJ HYV GdYfGhjjf hGdcdeGJ HGdMeQI s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs